Juridical Review of The Term Limitation of Political Party Chairman to Realize Constitutional Democracy in Indonesia - Adhiba, Lingga Zalfa; Wedhatami, Bayangsari (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
Political parties are crucial institutions in Indonesian democracy, but the absence of term limits for party chairpersons has the potential to create power domination, oligarchy, and weakening of internal party mechanisms. This study analyzes the urgency of limiting the term of office of political party chairmen and formulates ideal norms in the positive legal system in Indonesia. The results show that the absence of this regulation has triggered individual domination, such as prolonged leadership in PDIP and NasDem, barriers to regeneration, and misappropriation. Article 1 Paragraph (2) and Article 28E Paragraph (3) of the 1945 Constitution juridically become the constitutional basis, even though Law No. 2 Of 2011 on the Amendment to Law No. 2 Of 2008 on Political Parties does not explicitly regulate it. The author recommends: (1) revising the Article 23 Paragraph (1) of the Political Party Law to limit the term of office of the party chairman to a maximum of two terms and 5 years in office; (2) an independent supervision mechanism; (3) transparency of the succession process; and (4) the application of sanctions for violating parties. The implementation of this policy is expected to strengthen constitutional democracy, prevent oligarchy, and encourage the political participation of the younger generation. Cooperation between the government and civil society is needed to realize constitutional democracy in Indonesia.